Praktikalitas Media Pembelajaran Matematika pada Materi Aljabar Berbasis Pendekatan PMRI - Elisyah, Nur; Mutia Fonna; Desy Sary Ayunda (Indo-MathEdu Intellectuals Journal, 2024)
The difficulty of students understanding algebra material is a very important problem to overcome. This is because algebra material is so important which is very useful in every science, one of which is economics. To find out the practicality of mathematics learning media in algebra material based on the PMRI approach is the aim of this research. The methodology in this research is development research using the Tessmer method. In the Tessmer method, there are two research procedures, namely, the preliminary (preparation) stage and the formative evaluation stage. Practicality lies in the formative evaluation stage in the small group section. At the small group stage, prototype II was tested on five class VII middle school students. The data collection technique in this research is a student response questionnaire and documents. Based on the results of the student response questionnaire, an average score percentage of 88,575 % was obtained, which means it falls within the very practical criteria. Apart from that, it is also strengthened by the results of researchers' observations which show that students can use mathematics learning media on PMRI-based algebra material easily and well.